2017
DOI: 10.1530/jme-16-0202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of G6pc2 deletion on body weight and cholesterol in mice

Abstract: Genome wide association study (GWAS) data have linked the G6PC2 gene to variations in fasting blood glucose (FBG). G6PC2 encodes an islet-specific glucose-6-phosphatase catalytic subunit that forms a substrate cycle with the beta cell glucose sensor glucokinase. This cycle modulates the glucose sensitivity of insulin secretion and hence FBG. GWAS data have not linked G6PC2 to variations in body weight but we previously reported that female C57BL/6J G6pc2 knockout (KO) mice were lighter than wild-type littermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Plasma cholesterol ( Figure 4 B), FPI ( Figure 4 C) and FBG ( Figure 4 D) were all significantly elevated following high fat diet feeding. The elevation in plasma cholesterol was greater in WT than KO mice after 84 days on the diet ( Figure 4 B), as previously reported [ 23 ]. The elevation in FBG in WT and KO mice was apparent after 28 days of high fat diet feeding and the significant difference in FBG between WT and G6pc2 KO mice remained after 84 days ( Figure 4 D).…”
Section: Resultssupporting
confidence: 89%
“…Plasma cholesterol ( Figure 4 B), FPI ( Figure 4 C) and FBG ( Figure 4 D) were all significantly elevated following high fat diet feeding. The elevation in plasma cholesterol was greater in WT than KO mice after 84 days on the diet ( Figure 4 B), as previously reported [ 23 ]. The elevation in FBG in WT and KO mice was apparent after 28 days of high fat diet feeding and the significant difference in FBG between WT and G6pc2 KO mice remained after 84 days ( Figure 4 D).…”
Section: Resultssupporting
confidence: 89%
“…Animal studies investigating G6PC2 function in vivo and ex vivo have demonstrated its role in regulating fasting blood glucose and glucose stimulated insulin secretion (GSIS). Thus, germline G6pc2 null mice and mice with β-cell-specific ablation of G6pc2 display significantly reduced fasting blood glucose levels, in support of the notion that G6PC2 encodes the effector transcript identified by the aforementioned GWAS studies (12,13,(20)(21)(22). Moreover, pancreatic islets from G6pc2 null mice exhibit higher insulin secretion at submaximal glucose concentrations, consistent with a leftward shift of the dose response curve for GSIS (13).…”
Section: Introductionsupporting
confidence: 72%
“…Instead, we think the explanation for the lack of an association lies in the fact that G6PC2 regulates the glucose sensitivity of GSIS. This creates a situation in which reduced G6PC2 protein expression lowers FBG without affecting fasting plasma insulin ( 8 , 9 , 11 , 12 ). Because this reduced FBG would be associated with unchanged glycolytic flux, we previously speculated ( 9 ) that it would therefore also be associated with no change in generation of damaging reactive oxygen species (ROS) that appear sufficient to drive beta cell failure ( 46 , 47 ), explaining the lack of association with T2D risk.…”
Section: Discussionmentioning
confidence: 99%
“…Key evidence in support of this model are the observations that, in isolated G6pc2 knockout (KO) islets, glucose-6-phosphatase activity ( 8 ) and glucose cycling ( 10 ) are both reduced, whereas glycolysis is elevated ( 9 ). Deletion of G6pc2 results in a leftward shift in the dose–response curve for GSIS ( 8 ) such that under fasting conditions, insulin levels are the same in wild-type (WT) and G6pc2 KO mice, but FBG is reduced in KO mice ( 8 , 9 , 11 , 12 ). These observations are consistent with genome-wide association studies (GWAS) and molecular studies that have linked the rs560887 “A” allele to reduced G6PC2 expression and reduced FBG ( 13 , 14 , 15 , 16 ).…”
mentioning
confidence: 99%